Aplicação de ferramentas de bioinformática e bancos de dados públicos no design de primers para identificação de Limnoperna fortunei e avaliação de seu histórico de invasões - Baggi, Rafael Barrichello (Universidade Federal de São Carlos, 2025)
The golden mussel Limnoperna fortunei is an invasive exotic species that causes significant environmental, economic, and operational impacts on aquatic ecosystems and hydroelectric infrastructure in South America, making its early detection essential for monitoring and management actions. In this work, specific primers for the molecular identification of L. fortunei were developed in silico using bioinformatics tools and public genetic databases. One hundred and sixty-five sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene from the species, originating from different geographic regions, were obtained and analyzed, in addition to sequences from other representatives of the Mytilidae family, with the aim of evaluating genetic diversity, reconstructing phylogenetic relationships, and supporting the design of primers with high specificity. The sequences were aligned, filtered for quality, and used for Bayesian phylogenetic analyses, haplotype network construction, and calculation of genetic diversity parameters. The results confirmed high haplotype diversity associated with low nucleotide diversity, a pattern consistent with recent population expansion, as well as congruence between the phylogeny based on the COI gene and previously published mitogenomic phylogenies for Mytilidae. From the consensus sequences, two primer pairs were designed, one targeting the complete barcode region and the other the minicode region of the COI gene, both evaluated for physicochemical parameters and specificity in silico. The developed primers were subjected to in vitro tests by conventional PCR, using different DNA concentrations and a wide gradient of annealing temperatures. However, no specific amplification was observed under any of the tested conditions, indicating possible limitations related to the presence of inhibitors, the quality of the extracted DNA, or the need for additional adjustments in primer design and PCR conditions. Despite the absence of experimental amplification, the study demonstrates the potential of the integrated use of public databases, phylogenetic analyses, and bioinformatics tools in the rational development of specific primers for invasive species. The results obtained provide relevant theoretical and methodological support for future molecular detection studies of L. fortunei, especially in approaches based on environmental DNA (eDNA), contributing to the improvement of monitoring and control strategies for this species.
Application of bioinformatics tools and public databases in the design of primers for the identification of Limnoperna fortunei and evaluation of its invasion history
Keywords: Mexilhão-dourado; Golden mussel; Bivalve; Espécies invasoras; Invasive exotic species; DNA barcoding; Citocromo c oxidase; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL; 14. Vida na Água